Conventional-Dose versus High-Dose Chemotherapy for Relapsed Germ Cell Tumors - Deaglan J. McHugh; Darren R. Feldman (Advances in Urology)
The majority of metastatic germ cell tumors (GCTs) are cured with cisplatin-based chemotherapy, but 20–30% of patients will relapse after first-line chemotherapy and require additional salvage strategies. The two major salvage approaches in this scenario are high-dose chemotherapy (HDCT) with autologous stem cell transplant (ASCT) or conventional-dose chemotherapy (CDCT). Both CDCT and HDCT have curative potential in the management of relapsed/refractory GCT. However, due to a lack of conclusive randomized trials, it remains unknown whether sequential HDCT or CDCT represents the optimal initial salvage approach, with practice varying between tertiary institutions. This represents the most pressing question remaining for defining GCT treatment standards and optimizing outcomes. The authors review prognostic factors in the initial salvage setting as well as the major studies assessing the efficacy of CDCT, HDCT, or both, describing the strengths and weaknesses that formed the rationale behind the ongoing international phase III “TIGER” trial.